Intra-oral approach for excision of an unusual cystic mass in a 12-year-Old girl: A case report - Nasem Jamal Yousef; Issa Saad; Marwan Al-Raeei; Chadi Azmeh; Maya Saad; Zeina Darwich (Oral Oncology Reports)
Central giant cell tumors (CGCTs) are uncommon benign tumors that affect the bones in the jaw. They mainly occur in females, typically before the age of 20. Diagnosis involves assessing the patient's medical history, conducting a physical examination, and performing radiological tests. Treatment options depend on factors such as the size and location of the tumor, as well as the symptoms experienced by the patient. Surgery is usually the primary approach. The prognosis for CGCTs is generally good, as they pose a low risk of malignancy. It is recommended to consult with a healthcare professional for an accurate diagnosis and personalized treatment plan. We present a case study of a pediatric patient who was diagnosed with an aggressive central giant cell cyst in their mandible, and describe how it was managed. CGCTs typically occur in adolescents aged 5–10 years. The patient in this case was a 12-year-old female who had a slowly progressing, non-pulsatile swelling of the mandible. During an intraoral examination, mobility of the teeth was observed, along with gingival swelling. The clinical behavior of CGCTs can vary, ranging from slow-growing and asymptomatic swellings to aggressive lesions causing pain, local osteolysis, root resorption, and tooth displacement. Giant cell tumors are commonly found in the epiphysis of long bones, making their localization in the mandible exceptional. Surgical excision is the main treatment for giant cell tumors, and various surgical approaches have been reported in the literature, depending on factors such as the cyst's size, location, and the surgeon's experience. However, there have been recent advancements in therapeutic options. Nonsurgical treatments like alpha-interferon, calcitonin, and corticosteroids have been described, and their advantages may be worth considering. Giant cyst tumors of the jaw are rare, especially in childhood. Their clinical behavior can vary greatly. The main treatment is surgical removal, and regular follow-ups are needed to monitor for any recurrence.